Портрет и вокруг - Маканин Владимир Семенович (Лауреаты литературных премий, 2009)
Экземпляры: абонемент (20240402) / Инвентарный номер: 37975 / Цена: / Авт.знак: М 15 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44